Slaves, Freedpersons, and Parables Two Notes on a Recent Study of the Shepherd of Hermas, Similitude 5 - Lookadoo, Jonathon 1987- (2021)
This article advances scholarship on Hermas’s social status by developing two suggestions from Mary Ann Beavis’s recent study of Herm. Sim. 5.2.2-11 (55.2-11). It first reads the exchange between the freedman and slaves (Herm. Sim. 5.2.9-10 [55.9-10]) and the reciprocity between rich and poor (Herm. Sim. 2.5-7 [51.5-7]) as attempts to uphold the traditional value of reciprocal gift-giving. It then explores the parable’s christological interpretation (Herm. Sim. 5.5.2-5.6.4 [58.2-59.4]) as a description of the Son’s salvific work in terms familiar to a freedperson’s experience. These elements are best understood if Hermas is a freedman in the Shepherd.